Electrochemical preparation method of staggered cuprous oxide micron cubes
Through room temperature redox reaction and electrochemical treatment, a high crystalline interlaced cuprous oxide microcube material was prepared, which solved the problems of limited preparation methods for microcube oxide and single morphology in the prior art, and achieved efficient preparation and wide application of materials.
Patent Information
- Application Number
- CN202411985198.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, the methods for preparing micron cuprous oxide are limited, and the product morphology is single, making it difficult to meet the application needs in the fields of photocatalysis, photothermal, etc.
A room temperature redox reaction was used, clean foamed copper oxide microcube material was prepared by reacting in a mixed solution of alkaline solution and persulfate by electrochemical treatment in the three electrode system.
It realizes the efficient preparation of interlaced cuprous oxide micron cube materials. The material has a high area specific capacity, is suitable for supercapacitors, and has stable chemical properties, and is suitable for applications in multiple fields.
Smart Images

Figure CN119776940A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electrode material preparation, and in particular relates to an electrochemical preparation method of interlaced cuprous oxide micrometer cubes. Background Art
[0002] Cuprous oxide is an important copper compound with unique physical and chemical properties and is widely used in many fields. There are many technical routes for the preparation of cuprous oxide, such as chemical precipitation, solvent thermal method, reduction method, etc. The morphology of cuprous oxide can be regulated by a specific preparation method. For example, hydrothermal synthesis can prepare cuprous oxide with different morphologies such as nanopowders, nanowires, and nanosheets. The cuprous oxide morphology usually obtained by the precipitation method is granular. The sol-gel method may prepare cuprous oxide with a porous structure. In addition, the crystal form of cuprous oxide can also be spherical, octahedral, cubic, etc., and the formation of these forms is also affected by the preparation method and conditions. In practical applications, a suitable preparation method can be selected as needed to obtain cuprous oxide with a specific morphology.
[0003] Most of the reports in the current literature are about nano cuprous oxide, and the synthesis methods are diverse. However, there are few technical studies on how to prepare micron cuprous oxide. Some studies have prepared cuprous oxide microrods by hydrothermal method using cupric sulfate pentahydrate as copper source and D-sorbitol as reducing agent (Functional Materials, 2007, 38, 2255-2256.). Using cupric chloride as copper source, sodium acetate as precipitant, polyethylene glycol as morphology control agent, glucose as reducing agent, micron cuprous oxide cubes were prepared by hydrothermal method in a mixed solvent formed by water and ethylene glycol (Chemical Research and Application, 2013, 25, 525-528.). Micron cuprous oxide has broad application prospects in the fields of photocatalysis and photothermal, and its unique morphology enables it to show excellent performance in these fields. Therefore, the controllable preparation of micron cuprous oxide is of great significance. Summary of the invention
[0004] In view of the fact that the existing methods for preparing micron cuprous oxide are limited and have the disadvantage of single product morphology, the purpose of the present invention is to provide an electrochemical preparation method of interlaced cuprous oxide micron cubes, which has the advantages of simple preparation process, easy operation, short preparation cycle, energy saving, high efficiency and low cost. At the same time, the prepared interlaced cuprous oxide micron cube material has a high area specific capacity when used as a supercapacitor electrode material.
[0005] To achieve the above technical purpose, the present invention has made unremitting efforts through a large number of experimental studies, and finally uses the redox reaction at room temperature as the main synthesis mechanism, clean foam copper as the copper source, reacts in a mixed solution of alkaline solution and persulfate for a certain time, and sequentially washes, vacuum-dries, and calcines the foam copper intermediate; then, in a three-electrode system, the treated foam copper is used as the working electrode, and it is electrochemically treated in a selenious acid solution to prepare a highly crystalline cuprous oxide material, which presents a staggered micrometer cube morphology, and the surface of the cube is smooth and flat.
[0006] Specifically, the object of the present invention is achieved according to the following technical solution: an electrochemical preparation method of staggered cuprous oxide microcubes, the method comprising the following steps:
[0007] Step 1, ultrasonically cleaning the cut copper foam in acetone, hydrochloric acid, and deionized water in sequence, wiping it dry, and then vacuum drying it at 50-60° C. for 3-6 hours;
[0008] Step 2, placing the copper foam obtained in step 1 in a mixed solution of an alkaline solution and a persulfate solution, wherein the molar ratio of hydroxide ions in the alkaline solution to persulfate ions in the persulfate solution is (100-200):1, reacting at room temperature for 12-36 minutes, turning over every 5-7 minutes, washing the obtained copper foam intermediate with deionized water after the reaction, and then vacuum drying at 50-60° C. for 3-6 hours;
[0009] Step 3, arranging the copper foam intermediate monolayer obtained in step 2 in a porcelain boat in sequence, heating the temperature to 190-230° C. at a heating rate of 2-10° C. / min in a muffle furnace, and calcining for 1.5-3.5 h;
[0010] Step 4: electrochemically treat the copper foam obtained in step 3 in a three-electrode system using a 14.4-54.1 mmol / L selenious acid solution as an electrolyte, then wash with deionized water, and vacuum dry at 50-60°C for 3-6 hours to prepare an interlaced cuprous oxide microcube material supported on a copper foam substrate. The obtained material has an interlaced microcube morphology, and the surface of the cube is smooth and flat.
[0011] Further preferably, in the electrochemical preparation method of the interlaced cuprous oxide microcubes as described above, the specific operation of the drying treatment in step 1 is: the cleaned foam copper is sequentially displayed in a culture dish, and the enriched water on the surface is absorbed with lens cleaning paper.
[0012] Further preferably, in the electrochemical preparation method of the interlaced cuprous oxide microcubes as described above, the alkaline solution in step 2 is an aqueous solution of sodium hydroxide and / or potassium hydroxide.
[0013] Further preferably, in the electrochemical preparation method of the interlaced cuprous oxide microcubes as described above, the persulfate in step 2 is one or a mixture of two or more of sodium persulfate, potassium persulfate and ammonium persulfate.
[0014] Further preferably, in the electrochemical preparation method of the staggered cuprous oxide microcubes as described above, in step 3, the temperature is raised to 200-210° C. at a heating rate of 5-10° C. / min in a muffle furnace and calcined for 2.5-3.5 h.
[0015] Further preferably, in the electrochemical preparation method of the staggered cuprous oxide microcubes as described above, the preparation method of the selenious acid solution in step 4 is: adding selenium dioxide to deionized water, the mass ratio of selenium dioxide to deionized water is (0.0016-0.006): 1, and stirring at room temperature for 20-35 minutes.
[0016] Further preferably, in the electrochemical preparation method of the interlaced cuprous oxide microcubes as described above, the three-electrode system in step 4 is: the working electrode is the copper foam obtained in step 3, the counter electrode is a platinum sheet electrode, the reference electrode is an Ag / AgCl electrode, and the electrolyte is a selenious acid solution.
[0017] Still more preferably, in the electrochemical preparation method of the staggered cuprous oxide microcubes as described above, the three-electrode system in step 4 is: the working electrode is the copper foam obtained in step 3, and the counter electrode is 1.0*1.0 cm 2 The reference electrode is a platinum electrode, the reference electrode is an Ag / AgCl electrode, and the electrolyte is 50 mL of selenious acid solution.
[0018] Further preferably, in the electrochemical preparation method of the staggered cuprous oxide microcubes as described above, the parameters of the electrochemical treatment in step 4 are: cyclic voltammetry scanning is performed in a low voltage range of -1.3 to -1.0 V and a high voltage range of 0 to 0.3 V, and the scanning rate is 3 to 10 mV s -1 , the number of scanning circles is 2 to 6 circles.
[0019] In addition, the present invention also provides the above-mentioned staggered cuprous oxide microcube material prepared by an electrochemical preparation method and its application, which is to use the above-mentioned staggered cuprous oxide microcube in a supercapacitor.
[0020] Compared with the prior art, the staggered cuprous oxide microcube material prepared by the present invention has the following advantages and advancements:
[0021] (1) The present invention uses copper foam as a copper source, and the prepared interlaced cuprous oxide microcubes are in-situ grown on the copper foam, and can be directly used as an integrated electrode for supercapacitors.
[0022] (2) The micron-sized cuprous oxide synthesized by the present invention has the characteristics of stable chemical properties and is not easy to change, so that the material can maintain its original performance under a wide range of use conditions.
[0023] (3) The micron-sized cuprous oxide synthesized by the present invention has a unique morphology of interlaced cubes. This novel morphology gives it a unique application prospect of physical and chemical properties, and has great potential and value for application in multiple fields.
[0024] (4) The selenious acid used in the present invention has a certain reducing property. When combined with the electrochemical cyclic voltammetric dissolution deposition method, it has a dual synthetic advantage, which can realize the reduction of cupric oxide to cuprous oxide and the precise control of the dissolution and deposition process of cuprous oxide.
[0025] (5) Compared with other synthesis methods, the electrochemical method used in the present invention has the advantages of simple preparation process, easy operation, low synthesis temperature, etc., and also has the advantage of accurately controlling its structure by adjusting the electrochemical parameters.
[0026] (6) When the material prepared by the present invention is directly used as an integral electrode as a supercapacitor positive electrode material, it can exhibit excellent area specific capacity, and can provide innovative technical support for the development of high-performance supercapacitors, which has important research significance and application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is an XRD diagram of an interlaced cuprous oxide microcube material prepared in Example 1 of the present invention;
[0028] Figure 2 This is one of the SEM images of a staggered cuprous oxide microcube material prepared in Example 1 of the present invention;
[0029] Figure 3 This is the second SEM image of a staggered cuprous oxide microcube material prepared in Example 1 of the present invention;
[0030] Figure 4 This is the third SEM image of a staggered cuprous oxide microcube material prepared in Example 1 of the present invention;
[0031] Figure 5 CV curves of a staggered cuprous oxide microcube material prepared in Example 1 of the present invention at different scanning speeds;
[0032] Figure 6 This is a GCD curve of an interlaced cuprous oxide microcube material prepared in Example 1 of the present invention at different current densities.
[0033] Figure 7The staggered cuprous oxide microcube material prepared in Example 1 of the present invention is subjected to a current density of 30 mA cm -2 Cyclic stability test curve.
[0034] Figure 8 This is a SEM image of a staggered cuprous oxide microcube material prepared in Example 2 of the present invention;
[0035] Fig. 9 This is a SEM image of a staggered cuprous oxide microcube material prepared in Example 3 of the present invention;
[0036] Fig.10 This is a SEM image of a staggered cuprous oxide microcube material prepared in Example 4 of the present invention;
[0037] Fig.11 This is a SEM image of a staggered cuprous oxide microcube material prepared in Example 5 of the present invention;
[0038] Fig.12 This is a SEM image of an interlaced cuprous oxide microcube material prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0039] The preparation method of the present invention is described in detail below in conjunction with the accompanying drawings and specific examples, but the protection scope of the present invention is not limited to the following examples.
[0040] Embodiment 1:
[0041] An electrochemical preparation method of staggered cuprous oxide microcubes is specifically carried out according to the following steps:
[0042] Step 1, ultrasonically clean the cut copper foam (1.0 cm*1.0 cm) in acetone, 1.0 mol / L hydrochloric acid solution, and deionized water in sequence, and place the cleaned copper foam in a culture dish in sequence, absorb the enriched water on its surface with lens cleaning paper, and vacuum dry it at 60°C for 6 hours;
[0043] Step 2, taking 1 piece of copper foam obtained in step 1, placing it in 20 mL of a mixed solution of potassium hydroxide and potassium persulfate, wherein the concentration of potassium hydroxide in the mixed solution is 1.2 mol / L and the concentration of potassium persulfate is 0.012 mol / L, reacting at room temperature for 18 min, turning over once every 6 min, washing the copper foam intermediate with deionized water, and vacuum drying at 60° C. for 6 h;
[0044] Step 3, the copper foam intermediate monolayer obtained in step 2 is arranged in sequence in a porcelain boat, and the temperature is raised to 210° C. at a heating rate of 5° C. / min in a muffle furnace, and calcined for 2.5 hours.
[0045] Step 4: Add 100 mg of selenium dioxide to 50 mL of deionized water and stir at room temperature for 30 min to obtain a selenious acid solution, which is used as the electrolyte. In the three-electrode system, the copper foam obtained in step 3 is used as the working electrode, the 1.0*1.0 cm 2 The platinum electrode was used as the counter electrode and the Ag / AgCl electrode was used as the reference electrode. Cyclic voltammetry was performed in the low voltage range of -1.1 V and the high voltage range of 0.1 V at a scan rate of 5 mV s -1 The scanning number is 2. Then, the sample was washed with deionized water and dried under vacuum at 60°C for 6 h to prepare staggered cuprous oxide microcube material supported on the copper foam substrate.
[0046] Embodiment 2:
[0047] An electrochemical preparation method of staggered cuprous oxide microcubes is specifically carried out according to the following steps:
[0048] Step 1, ultrasonically clean the cut copper foam (1.0 cm*1.0 cm) in acetone, 1.0 mol / L hydrochloric acid solution, and deionized water in sequence, and place the cleaned copper foam in a culture dish in sequence, absorb the enriched water on its surface with lens cleaning paper, and vacuum dry it at 60°C for 6 hours;
[0049] Step 2, taking 1 piece of copper foam obtained in step 1, placing it in 20 mL of a mixed solution of sodium hydroxide and sodium persulfate, wherein the concentration of sodium hydroxide in the mixed solution is 1.2 mol / L and the concentration of sodium persulfate is 0.012 mol / L, reacting at room temperature for 18 min, turning over once every 6 min, washing the copper foam intermediate with deionized water, and vacuum drying at 60° C. for 6 h;
[0050] Step 3, the copper foam intermediate monolayer obtained in step 2 is arranged in sequence in a porcelain boat, and the temperature is raised to 200° C. at a heating rate of 5° C. / min in a muffle furnace, and calcined for 3.5 hours.
[0051] Step 4: Add 100 mg of selenium dioxide to 50 mL of deionized water and stir at room temperature for 30 min to obtain a selenious acid solution, which is used as the electrolyte. In the three-electrode system, the copper foam obtained in step 3 is used as the working electrode, the 1.0*1.0 cm 2 The platinum electrode was used as the counter electrode and the Ag / AgCl electrode was used as the reference electrode. Cyclic voltammetry was performed in the low voltage range of -1.2 V and the high voltage range of 0.2 V at a scan rate of 5 mV s -1 The scanning number is 3. Then, the sample was washed with deionized water and dried under vacuum at 60°C for 6 h to prepare staggered cuprous oxide microcube material supported on the foam copper substrate.
[0052] Embodiment 3:
[0053] An electrochemical preparation method of staggered cuprous oxide microcubes is specifically carried out according to the following steps:
[0054] Step 1, ultrasonically clean the cut copper foam (1.0 cm*1.0 cm) in acetone, 1.0 mol / L hydrochloric acid solution, and deionized water in sequence, and place the cleaned copper foam in a culture dish in sequence, absorb the enriched water on its surface with lens cleaning paper, and vacuum dry it at 60°C for 6 hours;
[0055] Step 2, taking 1 piece of copper foam obtained in step 1, placing it in 20 mL of a mixed solution of potassium hydroxide and potassium persulfate, wherein the concentration of potassium hydroxide in the mixed solution is 1.2 mol / L and the concentration of potassium persulfate is 0.008 mol / L, reacting at room temperature for 24 min, turning over once every 6 min, washing the copper foam intermediate with deionized water, and vacuum drying at 60° C. for 6 h;
[0056] Step 3, the copper foam intermediate monolayer obtained in step 2 is arranged in sequence in a porcelain boat, and the temperature is raised to 220° C. at a heating rate of 10° C. / min in a muffle furnace, and calcined for 2.0 h.
[0057] Step 4: Add 100 mg of selenium dioxide to 50 mL of deionized water and stir at room temperature for 30 min to obtain a selenious acid solution, which is used as the electrolyte. In the three-electrode system, the copper foam obtained in step 3 is used as the working electrode, the 1.0*1.0 cm 2 The platinum electrode was used as the counter electrode and the Ag / AgCl electrode was used as the reference electrode. Cyclic voltammetry was performed in the low voltage range of -1.2 V and the high voltage range of 0.2 V at a scanning rate of 10 mV s -1 The scanning number is 6. Then, the sample was washed with deionized water and dried under vacuum at 60°C for 6 h to prepare staggered cuprous oxide microcube material supported on the copper foam substrate.
[0058] Embodiment 4:
[0059] An electrochemical preparation method of staggered cuprous oxide microcubes is specifically carried out according to the following steps:
[0060] Step 1, ultrasonically clean the cut copper foam (1.0 cm*1.0 cm) in acetone, 1.0 mol / L hydrochloric acid solution, and deionized water in sequence, and place the cleaned copper foam in a culture dish in sequence, absorb the enriched water on its surface with lens cleaning paper, and vacuum dry it at 60°C for 6 hours;
[0061] Step 2, taking 1 piece of copper foam obtained in step 1, placing it in 20 mL of a mixed solution of potassium hydroxide and ammonium persulfate, wherein the concentration of potassium hydroxide in the mixed solution is 1.2 mol / L and the concentration of ammonium persulfate is 0.006 mol / L, reacting at room temperature for 30 min, turning over once every 6 min, washing the copper foam intermediate with deionized water, and vacuum drying at 60° C. for 6 h;
[0062] Step 3, the copper foam intermediate monolayer obtained in step 2 is arranged in sequence in a porcelain boat, and the temperature is raised to 190° C. at a heating rate of 5° C. / min in a muffle furnace, and calcined for 3.5 hours.
[0063] Step 4: Add 300 mg of selenium dioxide to 50 mL of deionized water and stir at room temperature for 30 min to obtain a selenious acid solution, which is used as the electrolyte. In the three-electrode system, the copper foam obtained in step 3 is used as the working electrode, and the 1.0*1.0 cm 2 The platinum electrode was used as the counter electrode and the Ag / AgCl electrode was used as the reference electrode. Cyclic voltammetry was performed in the low voltage range of -1.1 V and the high voltage range of 0.1 V at a scan rate of 3 mV s -1 The scanning number is 2. Then, the sample was washed with deionized water and dried under vacuum at 60°C for 6 h to prepare staggered cuprous oxide microcube material supported on the copper foam substrate.
[0064] Embodiment 5:
[0065] An electrochemical preparation method of staggered cuprous oxide microcubes is specifically carried out according to the following steps:
[0066] Step 1, ultrasonically clean the cut copper foam (1.0 cm*1.0 cm) in acetone, 1.0 mol / L hydrochloric acid solution, and deionized water in sequence, and place the cleaned copper foam in a culture dish in sequence, absorb the enriched water on its surface with lens cleaning paper, and vacuum dry it at 60°C for 6 hours;
[0067] Step 2, taking 1 piece of copper foam obtained in step 1, placing it in 20 mL of a mixed solution of potassium hydroxide and potassium persulfate, wherein the concentration of potassium hydroxide in the mixed solution is 1.2 mol / L and the concentration of potassium persulfate is 0.006 mol / L, reacting at room temperature for 30 min, turning over once every 6 min, washing the copper foam intermediate with deionized water, and vacuum drying at 60° C. for 6 h;
[0068] Step 3, the copper foam intermediate monolayer obtained in step 2 is arranged in sequence in a porcelain boat, and the temperature is raised to 230° C. at a heating rate of 5° C. / min in a muffle furnace, and calcined for 1.5 h.
[0069] Step 4: Add 80 mg of selenium dioxide to 50 mL of deionized water and stir at room temperature for 30 min to obtain a selenious acid solution, which is used as the electrolyte. In the three-electrode system, the copper foam obtained in step 3 is used as the working electrode, and the 1.0*1.0 cm 2 The platinum electrode was used as the counter electrode and the Ag / AgCl electrode was used as the reference electrode. Cyclic voltammetry was performed in the low voltage range of -1.2 V and the high voltage range of 0.2 V at a scan rate of 5 mV s -1 The scanning number is 3. Then, the sample was washed with deionized water and dried under vacuum at 60°C for 6 h to prepare staggered cuprous oxide microcube material supported on the foam copper substrate.
[0070] Embodiment 6:
[0071] An electrochemical preparation method of staggered cuprous oxide microcubes is specifically carried out according to the following steps:
[0072] Step 1, ultrasonically clean the cut copper foam (1.0 cm*1.0 cm) in acetone, 1.0 mol / L hydrochloric acid solution, and deionized water in sequence, and place the cleaned copper foam in a culture dish in sequence, absorb the enriched water on its surface with lens cleaning paper, and vacuum dry it at 60°C for 6 hours;
[0073] Step 2, taking 1 piece of the copper foam obtained in step 1, placing it in 20 mL of a mixed solution of sodium hydroxide and potassium persulfate, wherein the concentration of sodium hydroxide in the mixed solution is 1.2 mol / L and the concentration of potassium persulfate is 0.008 mol / L, reacting at room temperature for 12 min, turning over once every 6 min, washing the copper foam intermediate with deionized water, and vacuum drying at 60° C. for 6 h;
[0074] Step 3, the copper foam intermediate monolayer obtained in step 2 is arranged in sequence in a porcelain boat, and the temperature is raised to 200° C. at a heating rate of 2° C. / min in a muffle furnace, and calcined for 3.5 hours.
[0075] Step 4: Add 80 mg of selenium dioxide to 50 mL of deionized water and stir at room temperature for 30 min to obtain a selenious acid solution, which is used as the electrolyte. In the three-electrode system, the copper foam obtained in step 3 is used as the working electrode, and the 1.0*1.0 cm 2 The platinum electrode was used as the counter electrode and the Ag / AgCl electrode was used as the reference electrode. Cyclic voltammetry was performed in the low voltage range of -1.3 V and the high voltage range of 0.0 V at a scanning rate of 5 mV s -1 The scanning number is 3. Then, the sample was washed with deionized water and dried under vacuum at 60°C for 6 h to prepare staggered cuprous oxide microcube material supported on the foam copper substrate.
[0076] like Figure 1The figure shows an XRD pattern of a staggered cuprous oxide micrometer cubic material prepared in Example 1 of the present invention, from which it can be seen that the synthesized material of the present invention is cuprous oxide, and the material has high crystallinity, wherein the diffraction peak of copper comes from the foam copper substrate.
[0077] like Figure 2 As shown, it is one of the SEM images of a staggered cuprous oxide micrometer cube material prepared in Example 1 of the present invention. It can be seen that the sample has a staggered micrometer cube morphology and is grown and loaded on a porous foam copper substrate.
[0078] like Figure 3 As shown, this is the second SEM image of an interlaced cuprous oxide microcube material prepared in Example 1 of the present invention. It can be seen that the sample has an interlaced microcube morphology with a particle size of 1 to 2 μm.
[0079] like Figure 4 As shown, this is the third SEM image of an interlaced cuprous oxide micrometer cube material prepared in Example 1 of the present invention. It can be seen that the sample has an interlaced micrometer cube morphology, and the surface of the cube is smooth and flat.
[0080] like Figure 5 As shown, it is a CV curve of an interlaced cuprous oxide microcube material prepared in Example 1 of the present invention. The curve has an obvious redox peak. As the scanning speed increases, the corresponding current increases successively.
[0081] like Figure 6 As shown in FIG. 1 , the GCD curve of a staggered cuprous oxide microcube material prepared in Example 1 of the present invention is shown. As the current density increases, the discharge time decreases. At a current density of 5 mA / cm 2 When the area specific capacity of the electrode is 1556mF / cm 2 .
[0082] like Figure 7 As shown in the figure, a staggered cuprous oxide microcube material prepared in Example 1 of the present invention is subjected to a current density of 30 mA cm -2 Cyclic stability test curve. After 5000 cycles, the capacity retention rate is 94.2%.
[0083] like Figure 8 As shown, it is a SEM image of an interlaced cuprous oxide micrometer cube material prepared in Example 2 of the present invention. It can be seen that the sample has an interlaced micrometer cube morphology, the surface of the cube is smooth, and the particle size is uniform.
[0084] like Fig. 9 As shown, it is a SEM image of an interlaced cuprous oxide micrometer cube material prepared in Example 3 of the present invention. It can be seen that the sample has an interlaced micrometer cube morphology and the particle size is reduced.
[0085] like Fig.10 As shown, it is a SEM image of an interlaced cuprous oxide microcube material prepared in Example 4 of the present invention. It can be seen that the sample has an interlaced microcube morphology and the degree of interlacing is increased.
[0086] like Fig.11 As shown, it is a SEM image of an interlaced cuprous oxide microcube material prepared in Example 5 of the present invention. It can be seen that the sample has an interlaced microcube morphology, the number of interlaced cubes increases, and there is a certain degree of stacking.
[0087] like Fig.12 As shown, it is a SEM image of an interlaced cuprous oxide microcube material prepared in Example 6 of the present invention. It can be seen that the sample has an interlaced microcube morphology, and the degree of interlacing is reduced.
Claims
1. An electrochemical preparation method of interlaced cuprous oxide microcubes, characterized in that: The method comprises the following steps: Step 1, ultrasonically cleaning the cut copper foam in acetone, hydrochloric acid, and deionized water in sequence, wiping it dry, and then vacuum drying it at 50-60° C. for 3-6 hours; Step 2, placing the copper foam obtained in step 1 in a mixed solution of an alkaline solution and a persulfate solution, wherein the molar ratio of hydroxide ions in the alkaline solution to persulfate ions in the persulfate solution is (100-200):1, reacting at room temperature for 12-36 minutes, turning over every 5-7 minutes, washing the obtained copper foam intermediate with deionized water after the reaction, and then vacuum drying at 50-60° C. for 3-6 hours; Step 3, arranging the copper foam intermediate monolayer obtained in step 2 in a porcelain boat in sequence, heating the temperature to 190-230° C. at a heating rate of 2-10° C. / min in a muffle furnace, and calcining for 1.5-3.5 h; Step 4, using 14.4-54.1 mmol / L selenious acid solution as electrolyte, electrochemically treating the copper foam obtained in step 3 in a three-electrode system, then washing with deionized water, and vacuum drying at 50-60° C. for 3-6 hours to prepare an interlaced cuprous oxide microcube material supported on a copper foam substrate.
2. The electrochemical preparation method of interlaced cuprous oxide microcubes according to claim 1, characterized in that: The specific operation of the drying treatment in step 1 is: the cleaned foam copper is arranged in a culture dish in sequence, and the enriched water on the surface is absorbed with lens cleaning paper.
3. The electrochemical preparation method of staggered cuprous oxide microcubes according to claim 1, characterized in that: The alkaline solution in step 2 is an aqueous solution of sodium hydroxide and / or potassium hydroxide.
4. The electrochemical preparation method of staggered cuprous oxide microcubes according to claim 1, characterized in that: The persulfate described in step 2 is one or a mixture of two or more of sodium persulfate, potassium persulfate and ammonium persulfate.
5. The electrochemical preparation method of interlaced cuprous oxide microcubes according to claim 1, characterized in that: In step 3, the temperature is raised to 200-210° C. at a heating rate of 5-10° C. / min in a muffle furnace and calcined for 2.5-3.5 hours.
6. The electrochemical preparation method of interlaced cuprous oxide microcubes according to claim 1, characterized in that: The preparation method of the selenious acid solution in step 4 is: add selenium dioxide into deionized water, the mass ratio of selenium dioxide to deionized water is (0.0016-0.006):1, and stir at room temperature for 20-35 minutes.
7. The electrochemical preparation method of staggered cuprous oxide microcubes according to claim 1, characterized in that: The three-electrode system in step 4 is as follows: the working electrode is the copper foam obtained in step 3, the counter electrode is a platinum electrode, the reference electrode is an Ag / AgCl electrode, and the electrolyte is a selenious acid solution.
8. The electrochemical preparation method of interlaced cuprous oxide microcubes according to claim 7, characterized in that: The three-electrode system in step 4 is as follows: the working electrode is the copper foam obtained in step 3, and the counter electrode is 1.0*1.0 cm 2 The reference electrode is a platinum electrode, the reference electrode is an Ag / AgCl electrode, and the electrolyte is 50 mL of selenious acid solution.
9. The electrochemical preparation method of staggered cuprous oxide microcubes according to claim 1, characterized in that: The parameters of the electrochemical treatment in step 4 are: cyclic voltammetry scanning at a low voltage range of -1.3 to -1.0 V and a high voltage range of 0 to 0.3 V, with a scanning rate of 3 to 10 mV s -1 , the number of scanning circles is 2 to 6 circles.
10. An interlaced cuprous oxide microcubic material prepared according to the method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Sulfur-doped three-dimensional porous cuprous oxide nano-material and application thereof to electrochemical hydrogen evolution reaction
CN106629814A
Carbon-coated heteroatom-doped copper-based composite hydrogen evolution catalyst preparation method
CN110302818A
Foamy copper in-situ growth copper oxide / cuprous oxide photocatalytic material as well as preparation method and application thereof
CN113546624A
Anion-cation double-doped catalyst as well as preparation method and application thereof
CN114892204A
Cuprous oxide nano array type photoelectrocatalysis cathode and preparation method and application thereof
CN117403264A